Benefits and applications of microwave-assisted synthesis of nitrogen containing heterocycles in medicinal chemistry. Issue 24 (7th April 2020) - Henary, Maged; Kananda, Carl; Rotolo, Laura; Savino, Brian; Owens, Eric A.; Cravotto, Giancarlo
Abstract : Nitrogen containing heterocycles are of immense research interest because they are often found as naturally occurring bioactive compounds. Abstract : Nitrogen containing heterocycles are of immense research interest because they are often found as naturally occurring bioactive compounds. The prominence of N-heterocycles makes it vital to develop methods to increase their synthetic efficiencies and probe the effects of their modifications on biological efficacy. Medicinal chemists have exploited microwave-assisted organic synthesis (MAOS) to facilitate the development of complex heterocyclic structures. MAOS is a growing synthetic methodology among medicinal chemists and has proven to be more efficient in terms of reaction yield, reaction time, product purity and environmental friendliness for many reactions when compared to conventional thermal methods for cycloaddition and selective functionalization. The importance of nitrogen containing ring systems in medicine cannot be understated, as such ring systems have shown to be applicable in compounds such as vitamins, herbicides, anti-fungal agents, anti-bacterial agents and anti-cancer agents, among other things. The significance of these applications has created an unprecedented need for more efficient synthetic methods. This review presents an overview of MAOS and its role in recent and pressing advancements for the synthesis of small- and medium-sized nitrogen containing heterocycles, including pyrroles, indoles, pyridines, pyrrolidines, imidazoles, pyrazoles, pyrazolines, lactams, and 1, 2, 3-triazoles, which are significant scaffolds for compounds with medicinal uses.